2022
DOI: 10.3389/fpls.2021.772708
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies of Salt Tolerance at Seed Germination and Seedling Stages in Brassica napus

Abstract: Most crops are sensitive to salt stress, but their degree of susceptibility varies among species and cultivars. In order to understand the salt stress adaptability of Brassica napus to salt stress, we collected the phenotypic data of 505 B. napus accessions at the germination stage under 150 or 215 mM sodium chloride (NaCl) and at the seedling stage under 215 mM NaCl. Genome-wide association studies (GWAS) of 16 salt tolerance coefficients (STCs) were applied to investigate the genetic basis of salt stress tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…GO analysis revealed that most genes were associated with the cellular process, the metabolic process, biological regulation, and response to stimulus ( Supplementary Figure 10 ). Moreover, we also found that the most of these candidate genes were significantly differentially expressed under salt stress according to the RNA-seq data (PRJCA008229, https://ngdc.cncb.ac.cn/omix/ ) (Zhang et al, 2022 ). The relative expression of some candidate genes under normal and salt conditions was taken as an example ( Figure 3D ; Supplementary Table 19 ), which was consistent with the previous study (Zhang et al, 2019 ), showing the accuracy of candidate gene prediction.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…GO analysis revealed that most genes were associated with the cellular process, the metabolic process, biological regulation, and response to stimulus ( Supplementary Figure 10 ). Moreover, we also found that the most of these candidate genes were significantly differentially expressed under salt stress according to the RNA-seq data (PRJCA008229, https://ngdc.cncb.ac.cn/omix/ ) (Zhang et al, 2022 ). The relative expression of some candidate genes under normal and salt conditions was taken as an example ( Figure 3D ; Supplementary Table 19 ), which was consistent with the previous study (Zhang et al, 2019 ), showing the accuracy of candidate gene prediction.…”
Section: Resultsmentioning
confidence: 93%
“…The broad sense heritability ( H 2 b ) of all traits is calculated as follows: H 2 b = /( + /n + /nr) where was the genotype variance, was the error variance, and was interaction between genetic and environmental effects. The estimates of H2b were analyzed by the AVOVA for ANOVA using the lmer function of the lme4 package by R environment ( https://www.r-project.org/ ) (Chen et al, 2014 ; Li et al, 2020 ; Zhang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 20 of 30 SNPs were detected simultaneously in two replicate experiments, indicating the reliability of these loci. Previous studies have explored the genetic basis of salt stress responses at the germination or seedling stage using traditional QTL mapping or GWAS analysis [13,[17][18][19][20][21][22][23]45]. Compared with the previous results, four SNPs (ChrA10: 15,189,187,15,189,200,15,189,284,15, 188, 859 bp) could be repeatedly detected at the seedling and mature stages [23], and controlled different traits, suggesting that the four SNPs are common loci that control the salt tolerance of rapeseed at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of next-generation sequencing (NGS) technology, the genome-wide association study (GWAS) has become an effective approach to map QTLs related to complex traits of crops and has been applied in various crops, such as rice, soybean, and B. napus [14][15][16]. Some QTLs and candidate genes associated with salt-tolerance-related traits at the germination and seedling stages [17][18][19][20][21][22][23] and yield-related traits [24][25][26] have gradually been identified through GWAS in B. napus. Although a number of QTLs and candidate genes have been identified for salt tolerance, the molecular mechanisms underlying the regulation of salt tolerance and yield remain unclear in B. napus.…”
Section: Introductionmentioning
confidence: 99%